Influence of traffic load and far-field seismic excitation in cables of cable-stayed bridge - Nor Ashikin, Muhamad Khairussaleh; Lee, Chong Hoe; Parke, Gerald A.R.; Roslina, Omar; Shariza, Mat Aris (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Bridges are always expose to the cyclic live loads in the form of moving traffic and wind loads. This could jeopardise the service life of the bridges peculiarly in fatigue. With the rise of seismic activities nowadays, bridges may become more susceptible to fatigue damage. Thus, in this study, the static and dynamic behaviour of a cable-stayed bridge in terms of fatigue of steel elements are addressed by focusing on the stress variation in stay cables due to the effects of moving traffic loads and ground motion excitations. Fatigue Load Model 4 (FLM 4) has been adopted as a dynamic response on the bridge subjected to moving load while a two set of ground motions considering horizontal and vertical motions from far-field faults has been used as seismic excitation on the bridge. The results of this study revealed the notable influence of traffic loads on stress variations of cable-stayed bridges with significant effects due to ground motions scaled to the expected return period.